Excited‐State Proton Transfer Can Tune the Color of Protein Fluorescent Markers. Issue 16 (11th September 2015) - Mancini, Daiana T.; Sen, Kakali; Barbatti, Mario; Thiel, Walter; Ramalho, Teodorico C.
Abstract: We show by quantum mechanical/molecular mechanical (QM/MM) simulations that phenylbenzothiazoles undergoing an excited‐state proton transfer (ESPT) can be used to probe protein binding sites. For 2‐(2′‐hydroxy‐4′‐aminophenyl)benzothiazole (HABT) bound to a tyrosine kinase, the absolute and relative intensities of the fluorescence bands arising from the enol and keto forms are found to be strongly dependent on the active‐site conformation. The emission properties are tuned by hydrogen‐bonding interactions of HABT with the neighboring amino acid T766 and with active‐site water. The use of ESPT tuners opens the possibility of creating two‐color fluorescent markers for protein binding sites, with potential applications in the detection of mutations in cancer cell lines. Abstract : Two‐color fluorescent markers : The addition of an excited‐state proton transfer (ESPT) tuner to a phenylbenzothiazole (PBT) derivative can be used to probe the active site of a kinase, as the intensities of the two fluorescence bands arising from the enol and keto forms of the PBT are strongly dependent on the active‐site conformation. The use of ESPT tuners opens the possibility of creating two‐color fluorescent markers, with potential application in cancer diagnostics.